Prognosis of project-based instructional package on public secondary school students’ academic achievement in economics in Ebonyi State, Nigeria - Ogala, A. Egwu; Chukwuma, O. Chukwu; Aliyu, H. Dalhatu; Inusa, Diana (Kashere Journal of Education, 2023)
The researcher investigated the prognosis of project-based instructional package on public secondary school students’ academic achievement in Economics in Ebonyi State, Nigeria. Three (3) specific purposes, three (3) research questions and three (3) hypotheses were formulated to guide the study. The study employed quasi-experimental research design and the population of the study was two thousand, nine hundred and one (2,901) senior secondary two (SS11) students in public secondary schools in Ebonyi State, Nigeria. The instrument for data collection was Economics Achievement Test (EAT). Data collected were analyzed using mean and standard deviation for all research questions and analysis of co-variance (ANCOVA) was applied to test the null hypotheses at alpha level of 0.05. The findings of the study revealed among others that students’ academic achievement in Economics improved significantly when taught using project-based instructional package. The implication of the study is that findings of the study justify the urgent need for public secondary school teachers to effectively apply project-based instructional package for Economics classroom instruction in order to improve students’ academic achievement in Economics in both internal and external examinations. Based on the findings of the study, the researcher recommended among other things that Economics teachers in public secondary schools need to re-access their classroom instructional practices which make students passive listeners and emphasize those practices that engage students in teaching and learning processes. Useful suggestions for further studies were made.